Funding Sources Of The Budget Deficit And Its Impact On Economic Growth In Syrian During The Period 1994-2012 - اسماعيل, رولا; عاقل, سماح (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The state budget in Syria experiences a structural deficit reflects the imbalance of the macroeconomic, and shows the weakness of the budget finance resources and the low public spending efficiency, it also reflects the failure of the economic and fiscal policies in facing that deficit. The research consists of two main parts, the first one includes a study of the evolution of the deficit in Syria during the studied period through analysis of the expenditures and revenues structure in order to diagnose the most important causes of the deficit, The second part includes a study of the ways of financing the deficit and the impact of the deficit on the economic growth in Syria. The study concludes that the problem of the state budget deficit in Syria is a structural deficit and has negative impacts on the economic growth. The state budget refers to many reasons, the most important of them are: the weakness of the tax administration, the tax evasion, the low efficiency of public and private spending.